2017
DOI: 10.1098/rsta.2017.0007
|View full text |Cite
|
Sign up to set email alerts
|

Attempted synthesis of ortho -phenylene phosphino-tritylium cations

Abstract: With the synthesis of -phenylene phosphino-tritylium cations as an objective, we generated (2-lithiophenyl)diphenylphosphine and (2-lithiophenyl)di-isopropylphosphine and allowed these organolithium reagents to react with benzophenone. The resulting phosphino-triarylcarbinols were allowed to react with HBF in the presence of trifluoroacetic anhydride in order to generate the corresponding cations. Instead of the targeted -phenylene phosphino-tritylium, the cations formed in these reactions were identified as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In other words,acarbenium ion should be am ore potent s-acceptor ligand, leading to ag reater enhancement in the hardness and Lewis acidity of the metal atom. Carbenium ions,which have already received interest as ligands for transition metals, [9] may also present ah igher chemical resilience,i np articular to oxidative conditions.W ith av iew to capitalize on these attributes,w e thus decided to reengage in carbenium chemistry [10] and explore the synthesis and properties of carbenium-based analogues [11] of known L/Z ambiphilic boron-containing ligands ( Figure 1C). [3a] Thec arbenium-based systems described herein bear similarities with phosphine ligands functionalized by carbon-based redox non-innocent moieties [12] while also adding to ongoing efforts in the chemistry of cationic phosphines as ligands for late-transition-metal catalysts.…”
mentioning
confidence: 99%
“…In other words,acarbenium ion should be am ore potent s-acceptor ligand, leading to ag reater enhancement in the hardness and Lewis acidity of the metal atom. Carbenium ions,which have already received interest as ligands for transition metals, [9] may also present ah igher chemical resilience,i np articular to oxidative conditions.W ith av iew to capitalize on these attributes,w e thus decided to reengage in carbenium chemistry [10] and explore the synthesis and properties of carbenium-based analogues [11] of known L/Z ambiphilic boron-containing ligands ( Figure 1C). [3a] Thec arbenium-based systems described herein bear similarities with phosphine ligands functionalized by carbon-based redox non-innocent moieties [12] while also adding to ongoing efforts in the chemistry of cationic phosphines as ligands for late-transition-metal catalysts.…”
mentioning
confidence: 99%
“…Gowda & Chen [7] apply FLPs in selective polymerizations of butyrolactones. Gabbaï and co-workers [8] report on efforts to combine carbon-Lewis acids with phosphines, while Stephan and co-workers [9] describe the use of gallium and indium Lewis acids in FLP chemistry. The issue is concluded with an article by Ashley and co-workers [10] in which they describe the activation of H 2 by a tin-based Lewis acid.…”
mentioning
confidence: 99%
“…Our original efforts toward the synthesis of such species focused on cations such as [o-Ph2P(C6H4)CPh2] + . 18 We found that this formulation actually existed as four-membered phosphonium species as a result of an intramolecular cyclization resulting from nucleophilic attack of the methylium carbon atom by the phosphino group. To disfavor phosphonium ion formation, we have now decided to pursue the introduction of methylium units where the carbocation is substantially stabilized as in the case of acridinium and xanthylium derivatives.…”
mentioning
confidence: 91%